Mapping staff perspectives towards the delivery of hospital care for children and young people with and without learning disabilities in England: a mixed methods national study - Kate Oulton; Faith Gibson; Lucinda Carr; Angela Hassiotis; Carey Jewitt; Charlotte Kenten; Jessica Russell; Mark Whiting; Irene Tuffrey-Wijne; Jo Wray (BMC, 2018)
Abstract Background Children and young people (CYP) with learning disabilities (LD) are a vulnerable population with increased risk of abuse and accidental injury and whose parents have reported concerns about the quality, safety and accessibility of their hospital care. The Care Quality Commission's (CQC) view of best practice for this group of patients includes: access to senior LD nurse provision; a clearly visible flagging system for identifying them; the use of hospital passports; and defined communication strategies (Glasper, Comp Child Adolesc Nurs 40:63-67, 2017). What remains unclear is whether these recommendations are being applied and if so, what difference they are making. Furthermore, what we do not know is whether parental concerns of CYP with LD differ from parents of other children with long-term conditions. The aims of this study were to 1) describe the organisational context for healthcare delivery to CYP with LD and their families and 2) compare staff perceptions of their ability to identify the needs of CYP with and without LD and their families and provide high quality care to effectively meet these needs. Methods Individual interviews (n = 65) and anonymised online survey (n = 2261) were conducted with hospital staff working with CYP in 15 children's and 9 non-children's hospitals in England. The majority of interviews were conducted over the telephone and recorded and transcribed verbatim. Health Research Authority was obtained and verbal or written consent for data collection was obtained from all interview participants. Results The nature and extent of organisational policies, systems and practices in place within hospitals to support the care of CYP with LD differs across England and some uncertainty exists within and across hospitals as to what is currently available and accessed. Staff perceived that those with LD were included less, valued less, and less safe than CYP without LD. They also reported having less confidence, capability and capacity to meet the needs of this population compared to those without LD. Conclusion Findings indicate inequality with regards the provision of high quality hospital care to children and young people with LD that meets their needs. There is a pressing need to understand the impact this has on them and their families. Trial registration The study has been registered on the NIHR CRN portfolio 20461 (Phase 1), 31336 (Phases 2-4).